Why Risk Assessments Fail. Issue 4 (3rd October 2017) - Engel, Barak
Abstract: In this article, we will examine in a light-hearted tone the chief reason why, in many organizations, risk assessments tend to be ineffective at driving actual, meaningful change, beyond fulfilling compliance requirements. While acknowledging the importance of identifying technical and operational risk areas, we focus on the lack of an appropriate, contextual business driver oriented discussion in a typical assessment, and how critical that missing communication can be to influencing important decision makers.